End-Users Satisfaction with Positive Deviance Approach as an Intervention to Promote Exclusive Breastfeeding in Jimma, Ethiopia: A Multi-Level Analysis - Siraneh Y; Woldie M; Birhanu Z (Dove Medical Press, 2022)
Yibeltal Siraneh,1 Mirkuzie Woldie,1,2 Zewdie Birhanu3 1Department of Health Policy and Management, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 2Fenot Project, Department of Population and Public Health, University of British Columbia, Addis Ababa, Ethiopia; 3Department of Health, Behavior and Society, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Yibeltal Siraneh, Email yibeltal_siraneh@yahoo.comBackground: Positive deviance approach (PDA) was implemented as an intervention strategy to address the poor practice of exclusive breastfeeding (EBF) in Jimma town, Ethiopia. Understanding the end-users satisfaction and its drivers is essential to determine whether this approach will be viable in the long run. Therefore, we determined the level of users' satisfaction with the intervention and identified multi-level predictors to explain variability.Methods: The data for this follow-up study were collected from September 01 to 25, 2020 among the study participants who were living in the intervention clusters of an earlier trial. A sample of 260 participants were invited to respond to an interviewer-administered structured questionnaire that assessed both individual and community-level variables. The developed tool was refined using experts' view (face validity) and using factor analysis (FA) to validate the satisfaction measurement scales (construct validity). The mean scores were standardized using Percentages Scale Mean Score (PSMS) formulae. Two-level mixed-effects linear regression (linear mixed models) were performed to fit individual, community, and mixed-level variables. All assumptions were checked for each analysis as appropriate and β-estimates at 95% CI and p-value of < 0.05 were considered to declare a level of significance.Results: The overall level of end-users' satisfaction (PSMS) with PDA as an intervention to improve EBF was 50.9% with a maximum score of 99% and a minimum of 8%. Of the emerged satisfaction measuring scales, the standardized mean score for the user empowerment scale was the highest (53.7%). Five scales were emerged with 84.2% of the total variability explained in users' satisfaction. The mixed-effect model revealed that age, occupation, experience of breastfeeding (BF), knowledge, attitude, self-efficacy, main source of BF information, previous home visit/support received from HEPs, participation in any social activities, and perceived community support for BF were independent two-level predictors of satisfaction.Conclusion: As an intermediate outcome, more than half of the end-users of the PDA intervention were satisfied. End-users' satisfaction with PDA as an intervention to promote EBF was predicted by multi-level factors. If they chose to use PDA as an intervention, Health program managers should be mindful of the two-level factors identified in this study.Keywords: intermediate outcome, user satisfaction, multi-level predictors, follow-up study, Ethiopia